Water displacement characteristics at the high water-cut stage based on microscopic experiments and simulations. (February 2021) - Sun, Hongxia; Yao, Jun; Zhao, Yujie
Based on microscopic water displacement experiments and numerical simulation results, new pore-scale displacement indexes were established and subsequently used to analyze oil and water flow characteristics and evaluate water displacement effectiveness. Thus, our understanding was deepened of remaining oil extraction by increasing liquid withdrawal and adjusting water-driving streamline at the high water-cut stage. Results show that water displacement is a process by which both pore sweep coefficient and inner-pore displacement coefficient are increasing simultaneously, resulting in the increase of microscopic comprehensive displacement efficiency. Preferential flow exists in the water displacement process. At the high water-cut stage, enlargement of velocity and pressure difference between the dominant and non-dominant flow channel indicates the injected water is channeling along the dominant flow channel, so that pore sweep coefficient grows slowly and even levels off, which slows down the increase of the comprehensive displacement efficiency. An inflection can be seen at remaining oil dispersion curve in high water-cut period which implies low utilization of the injected water and poor water displacement effectiveness. Increasing liquid withdrawal, to some extent, can decrease the pressure gap between the dominant and non-dominant flow channel and hence increase pore sweep coefficient. Adjusting water-drive streamline can greatly increase pore sweep coefficient by reducing the injected water channeling along the dominant flow channel and tapping the remaining oil in non-dominant flow channel, and therefore obtains a better response in improving water displacement efficiency.